Research on Goaf Retaining Technology of Double-Layer “Combined” Filling Body in High Gas Mine - Ning Huang; Xiao-Wu Zhang; Jiang-Hua Chen; Yang Liu; Hao Zhou; Jia-Jun Wen (Advances in Civil Engineering)
In high gas mines, the safety accidents of coal seam spontaneous combustion and gas leakage in goaf caused by fresh air flow entering goaf due to loose roof connection of filling body beside goaf are easy to occur. In order to solve such problems, this paper proposes the gob-retaining technology of the “combined” filling body at the side of the roadway. The upper layer of the “combined” filling body is constructed with high-water material as the “connecting top layer” so that the deformation form of the filling body is consistent with the broken characteristics of the roof, and the lower layer is constructed with concrete as the “supporting layer” to achieve sufficient support strength. The “combined” filling body can not only ensure the stability of roadway surrounding rock but also a timely closed goaf. The gob-retaining technology of the “combined” filling body was applied in the field of coal mine 2603 working face. Based on the engineering background, the mechanical model was established to calculate cutting resistance of the filling body, and Flac3D software was utilized to optimum parameters of the “combined” filling body. According to the field monitoring results, the “combined” filling wall at the side of the roadway effectively controls the stability of surrounding rock and the gas concentration in the roadway.